Photovoltaic properties of hybrid organic/inorganic semiconductor photodiode - Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2007)
An inorganic-organic photovoltaic device with a structure of [6,6]-phenyl C-61-butyric acid methyl ester and p-Si has been fabricated. The ideality factor value of the diode was found to be 2.12. This n value of the diode implies a deviation from ideal junction behavior. The p-Si/PCBM diode shows a photovoltaic behaviour with a maximum open circuit voltage V. of 0.12 V and short-circuit current IS, of 0.10 mu A under 6 mW/cm(2) light illumination. The parasitic resistances for the diode, which are series R-S and shunt R-sh resistances were calculated to be 5.24 x 10(4) Omega and 1.95 x 10(7) Omega, respectively. The capacitance-voltage plot indicates a non-linear behavior, suggesting a non-uniform dopant density profile and interface irregularities of p-Si/PCBM device. The barrier height Ob value for the diode was found to be 0.79 eV It is evaluated that the p-Si/PCBM diode is a photodiode with calculated electronic parameters. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: p-n heterojunction; photodiode; organic semiconductor